The Effect of Party Identification (Party-ID) on Split Ticket Voting (STV) in the 2019 Simultaneous Elections in West Sumatra - Pangi Syarwi; Ramlan Surbakti; Muhammad Asfar (GoAcademica Research & Publishing, 2026)
This study examines the effect of party identification (party-ID) on split-ticket voting behavior in the 2019 Simultaneous Presidential and Legislative Elections in West Sumatra Province, Indonesia. Split-ticket voting refers to the behavior of voters who split their choices between a political party in the legislative election and a presidential candidate from a different coalition in the executive election. Using a quantitative approach based on a field survey of 800 respondents, the findings reveal a significant negative relationship between party-ID and split-ticket voting. The stronger the voter’s identification with a particular party, the lower the likelihood of engaging in vote-splitting. These results align with the classic theory proposed in The American Voter and underscore the role of partisan affiliation as a key determinant of voting behavior. The study also highlights the contextual dynamics of Indonesia’s multiparty system, where weak party-ID contributes to the rise of pragmatic and candidate-centered voting patterns.